2021
DOI: 10.3389/fpsyg.2021.590283
|View full text |Cite
|
Sign up to set email alerts
|

“What If We Get Sick?”: Spanish Adaptation and Validation of the Fear of Illness and Virus Evaluation Scale in a Non-clinical Sample Exposed to the COVID-19 Pandemic

Abstract: Distinct sources of stress have emerged during the COVID-19 pandemic. Particularly, fear is expected to generate significant psychological burden on individuals and influence on either unsafe behavior that may hinder recovery efforts or virus-mitigating behaviors. However, little is known about the properties of measures to capture them in research and clinical settings. To resolve this gap, we evaluated the psychometric properties of a novel measure of fear of illness and viruses and tested its predictive val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
4
10
0
Order By: Relevance
“…The suggested structure for FIVE in the present study is based on its factor analysis and model fit indices. As a previous study [24] suggested four domains for items 1-19 (Fears of Getting Sick, Fears that Others May Get Sick, Fears of Concrete Limitations and Fears of not being able to meet the Basic Needs), our findings that were based on a sufficiently larger and sociodemographically different sample obtained a structure (Fears of Getting Sick; items 1-5, Fears that Others Get Sick; items 6-9 and Fears of the Impact on Social Life; items 10-19) that is somewhat different from that proposed in the Spanish version. On the other hand, when items 1-35 were analyzed, the data showed an improved fit in four domains that was slightly different from the one originally set by Ehrenreich-May.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…The suggested structure for FIVE in the present study is based on its factor analysis and model fit indices. As a previous study [24] suggested four domains for items 1-19 (Fears of Getting Sick, Fears that Others May Get Sick, Fears of Concrete Limitations and Fears of not being able to meet the Basic Needs), our findings that were based on a sufficiently larger and sociodemographically different sample obtained a structure (Fears of Getting Sick; items 1-5, Fears that Others Get Sick; items 6-9 and Fears of the Impact on Social Life; items 10-19) that is somewhat different from that proposed in the Spanish version. On the other hand, when items 1-35 were analyzed, the data showed an improved fit in four domains that was slightly different from the one originally set by Ehrenreich-May.…”
Section: Discussionsupporting
confidence: 53%
“…The conformity between subscales' items in the current Arabic version of FIVE examined in the present study is comparable to the Arabic Fear of COVID-19 Scale (FCV-19S) [28]. For instance, the internal consistency of Fears about Contamination and Illness subscale (items 1-9) was 0.89 and Fears about Social Distancing (items 10-19) was 0.91, which are relatively higher than that found in the Arabic FCV-19S [28] and Spanish FIVE [24]. The internal consistency of proposed structure of FIVE in Spanish language was α = 0.88 for Fears of Getting Sick from an illness or virus (items 1-4); α = 0.74 for Fears that Others May Get Sick from an illness or virus (items 5-9); α = 0.85 for Fears of Concrete Limitations due to an illness or virus (items 10,11,13,[15][16][17]; while the subscale Fears of not being able to meet Basic Needs of subsistence and work due to an illness or virus (items 12,14,18,19) had α = 0.79.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations